BELT CONVEYOR WEIGHT SCALE MEASUREMENT INFLUENCE FACTORS RESEARCH - Gailāns, Matīss; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
This paper is about belt conveyor weight scale measurement influence factors research. This research is very useful for loading fertilizer material, especially loading material to ships. If weight scale is calibrated wrong, it is possible to overload ship. At the beginning are overlooked main factors that effects weight scale measurements. Factors effect that are studied in terms of one year is air temperatures and relative air humidity’s influence on weight scale precision. Precision is controlled by comparing weight scale measurements and draft survey or dockets. At the end is two different possibilities for changing weight scale measurements knowing what kind of weather (temperature and humidity) will be for next ship, before loading calibrating weight scale.